The Relative indeterminacy of the inexcusable error and the effect on judicial independence - Reyna Zambrano, María Yokir (Frónesis, 2022)
Scientific reflection on ruling 3-19-CN / 20 has a philosophical-legal impact since it allows us to recognize that inexcusable error is a term without definition in the Ecuadorian legal system, used by the Council of the Judiciary, based on of the 2011 reforms to dismiss judges within a bureaucratic model, bypassing the jurisdictional power to resolve conflicts autonomously and independently, without internal or external interference, as a guarantee of protection. Criticisms from national and international organizations regarding interference in the justice system are constant. The National and Constitutional Court have ruled, the latter called for knowledge of an extraordinary protection action, which through judgment 3-19-CN / 20, resolved in a relative way the conditional constitutionality of the inexcusable error, after establishing differences between fraud, manifest negligence and inexcusable error. In its analysis, it resolves that the determination of the inexcusable error is the exclusive power of a higher level judge and not of the Council of the Judiciary, since there are rights that are under discussion. The inexcusable error is analyzed through a qualitative approach based on the documentary-bibliographic technique. The findings show that it is necessary for the judge to be autonomous in his decisions, as long as he does not fall into manifest negligence derived from arbitrariness in his actions. It concludes on the need to define the inexcusable error on the part of the legislator, to avoid affecting the justice system, and the security of citizens, judicial servants and judges.